Elucidation of Pseurotin Biosynthetic Pathway Points to Trans‐Acting C‐Methyltransferase: Generation of Chemical Diversity1. (18th June 2014) - Tsunematsu, Yuta; Fukutomi, Manami; Saruwatari, Takayoshi; Noguchi, Hiroshi; Hotta, Kinya; Tang, Yi; Watanabe, Kenji
Abstract Pseurotins comprise a family of structurally related Aspergillal natural products having interesting bioactivity. However, little is known about the biosynthetic steps involved in the formation of their complex chemical features. Systematic deletion of the pseurotin biosynthetic genes in A. fumigatus and in vivo and in vitro characterization of the tailoring enzymes to determine the biosynthetic intermediates, and the gene products responsible for the formation of each intermediate, are described. Thus, the main biosynthetic steps leading to the formation of pseurotin A from the predominant precursor, azaspirene, were elucidated. The study revealed the combinatorial nature of the biosynthesis of the pseurotin family of compounds and the intermediates. Most interestingly, we report the first identification of an epoxidase C‐methyltransferase bifunctional fusion protein PsoF which appears to methylate the nascent polyketide backbone carbon atom in trans.